Influence of annealing temperature on optical properties of Al doped ZnO nanoparticles via sol-gel methods - Rashid A.R.A.; Hazwani T.N.; Mukhtar W.M.; Taib N.A.M. (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus